Pengaruh Pupuk Silika Terhadap Pertumbuhan dan Produksi Kedelai pada Tanah Salin - Febryan Taufiq; Budi Adi Kristanto; Florentina Kusmiyati (Universitas Sebelas Maret, 2020)
Silica fertilizer is applied to the soil for the purpose of reducing the effects of salinity stress. This research study was conducted to examine the effect of fertilization ratio with different sources of silica to soybean growth and production on saline soil. The methods used was Completely Randomized Factorial Designs 2 x 6 with 3 replications. The first factor was soil salinity levels (A), consists of A1 (±3 dS/m) and A2 (±6 dS/m). The second factor was different silica fertilizer aplications (B) which consists of B0 (without silica), B1 (100% zeolite), B2 (75% zeolite, 25% liquid silica), B3 (50% zeolite, 50 % liquid silica), B4 (25% zeolite, 75% liquid silica), and B5 (100% liquid silica). Parameters observed in this research were plant height, number of leaves, number of pods, pod weight, number of seed and seed weight. Data was analyzed by analysis of variance followed by Duncan's Multiple Range Test. The result showed that the application of silica fertilizer through soil and leaves (50% zeolite, 50 % liquid silica) improved the growth and yield of soybean on soil with moderately saline (3 dS/m). application of silica fertilizer (50% zeolite, 50 % liquid silica) improved the growth and yield of soybean. The higher soil salinity reduced soybean growth and yield. Moreover, the utilization of silica minimized the decrease in soybean growth and yield.